Metoidioplasty in Gender Affirmation: A Review - Stojanovic, Borko; Bencic, Marko; Bizic, Marta; Djordjevic, Miroslav L. (Indian Journal of Plastic Surgery, 2022)
Metoidioplasty is a variant of the gender affirmation technique neophalloplasty, where a hormonally enlarged clitoris is reconstructed to become a small penis. The goals of metoidioplasty are male appearance of the genitalia, voiding in standing position, and completely preserved erogenous sensation of the neophallus. However, it does not enable penetrative sexual intercourse due to the small dimensions of the neophallus. Basic principles of metoidioplasty were established 50 years ago, and many refinements of the technique have been reported since. The latest improvements are based on the advances in urethroplasty, perioperative care, and new insights into female genital anatomy. The current metoidioplasty technique is a one-stage procedure that includes vaginectomy, straightening and lengthening of the clitoris, urethral reconstruction by combined flaps and grafts, and scrotoplasty with insertion of testicular implants. Good aesthetic, functional, and psychosexual outcomes are achieved with this type of neophalloplasty.
Keywords: transman; metoidioplasty; clitoris; urethroplasty; gender affirmation; neophalloplasty